2019
DOI: 10.1002/jmv.25529
|View full text |Cite
|
Sign up to set email alerts
|

Study of serum VEGF levels in patients with severe dengue infection admitted in a tertiary care hospital in Kolkata

Abstract: Dengue is the most common arboviral infection globally, but its pathogenesis is poorly explored. Vascular endothelial growth factor (VEGF) has an essential role in the host defense against viral infection. However, not much information is available regarding its status in dengue patients from the eastern zone of India. In the present investigation, the level of VEGF was investigated for its possible utility as a dengue severity marker. Accordingly, confirmed dengue cases were enrolled during 2016‐2018. Serum f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Nevertheless, the strong positive correlation between VEGF and IL-1RA serum levels was observed exclusively in non-neurological disease, suggesting a distinct mechanism of inflammation control in the neurological disorder. Elevated levels of serum VEGF were observed in children with viral encephalitis (51), in untreated patients with HIV-associated encephalopathy (52), and in patients with severe dengue (53,54). On the hand, EGF levels were increased in CSF of patients with neurological manifestations and did not show significant correlations with other molecules.…”
Section: Discussionmentioning
confidence: 94%
“…Nevertheless, the strong positive correlation between VEGF and IL-1RA serum levels was observed exclusively in non-neurological disease, suggesting a distinct mechanism of inflammation control in the neurological disorder. Elevated levels of serum VEGF were observed in children with viral encephalitis (51), in untreated patients with HIV-associated encephalopathy (52), and in patients with severe dengue (53,54). On the hand, EGF levels were increased in CSF of patients with neurological manifestations and did not show significant correlations with other molecules.…”
Section: Discussionmentioning
confidence: 94%
“…VEGF was the most widely studied growth factor. A total of 33 studies analyzed VEGF, and 22 found increased levels of VEGF in patients with dengue, most of them severe dengue, compared with nonsevere dengue and/or healthy controls [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ], including 5 studies in children only [ 16 , 17 , 21 , 26 , 27 ]. This trend of increased levels was maintained regardless of the disease classification, age group, or sample type.…”
Section: Resultsmentioning
confidence: 99%
“…Statistical analysis was performed using the Graph-Pad Prism statistics software (Graph-Pad Software Inc., San Diego, CA, USA free demo version 5.04) and all statistical methods were adopted from Patra et al, 2019 8,9 . Briefly, all data were subjected to ANOVA with post-hoc test for finding the significance of each study groups.…”
Section: Determination Of Serum Cytokine Titres In Serummentioning
confidence: 99%
“…a high level of IL6 and vasodilation agent vascular endothelial growth factor (VEGF) were noted in severe dengue patients 8,9 . In this study, we also investigate the status of another important vasodilating factor TNF-α.…”
mentioning
confidence: 99%